Estudo teórico da interação de gases na superfície de nanotubos de sno2 - Costa Júnior, Jorge Luiz (2016)
In this work we theoretically investigated the interactions of a tin dioxide nanotube obtained by the crystal plane (1 1 0), with gases CO, NH3, O2 e H2O separately. Using algorithms in programming language Shell bash, were performed playback of the gas molecules around the nanotube and through the semi-empirical method PM7 perform optimization and, along with the method ab initio B3LYP, the cluster energy calculation. Analyzing the variation of energy and the graphical representation of optimized cluster, there was interaction of gases with the nanotube. Through the energy eigenvalues obtained from the observed value calculations band gap of clusters, in order to determine variation in the conductivity of the material caused by adsorption of the gases to the nanotube. The gas CO, NH3 e H2O had studied the adsorption nanotube, demonstrating alignment of gas in relation to the negative nanotube and power variations, suggesting stability of the clusters, highlighting the interaction of the nanotube with ammonia molecules that had power variation equal -19,242 eV using ab initio method based on computer 3-21G. The values of band gap of the nanotube had decreased after the adsorption of gases. While experimental authors have observed the interaction of gas O2 in nanostructures SnO2, our results demonstrate the removal of gas in relation to the nanotube. The interaction of the molecules was carried out similarly to the nanotube SnO2, doped with manganese atoms, which showed interaction with all the molecules studied, particularly also for interaction with ammonia molecules, with greater variation in energy, suggesting greater stability.